The Influence of Work Period, Employment Status and Knowledge with Human Resource Performance in the Medical Records Unit at dr. Suyoto Hospital Pusrehab Jakarta - Sunarti, Sunarti; Pertiwi, Tria Saras; Hosizah, Hosizah (PROMOTOR, 2025)
This study examines the influence of work period, employment status, and knowledge on human resource performance in the medical records unit of Dr. Suyoto Pusrehab Hospital, Jakarta. The aim is to understand how much these three variables affect employee performance. Using a quantitative research method with a cross- sectional design, This study involved 34 respondents from medical records unit employees. Based on linear regression analysis, the results showed that all independent variables have an effect on the dependent variable. More clearly, it can be concluded that Work Period, Employee Status, and Knowledge have a significant effect (simultaneously) on Human Resource Performance in the Medical Records Work Unit of Dr. Suyoto Pusrehab Hospital (p<0,005).